New financial frontiers in housing: Innovation, accessibility, and tokenization in emerging markets - Francisco Vergara-Perucich; Carlos Aguirre-Nu\~nez (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
This paper examines how housing tokenization is discursively framed in Chile's digital public sphere, assessing whether it promotes affordability or reinforces financialization. Using a methodology that combines natural language processing, topic modeling, sentiment analysis, and semantic network analysis, the study analyzes content from 34 websites - including fintech startups, media outlets, and real estate firms - scraped and processed in R. Results show that tokenization is largely portrayed through a techno-optimistic lens focused on investment, trust, and digital innovation. Sentiment analysis highlights dominant emotional tones of "trust" and "anticipation," while topic modeling identifies four themes: return performance, platform ecosystems, asset commodification, and user empowerment. These narratives, however, tend to obscure critical perspectives on equity and governance. Despite limitations related to data bias and cultural nuance, the study offers a replicable method for analyzing technological discourses and raises important questions about the policy implications of financial innovation in emerging markets.
Keywords: G23; R31; O33; O16; 330; financial innovation; blockchain; real estate; token; financialization